Characterization of the multigene family coding for HMW glutenin subunits in wheat using cDNA clones. - Thompson, R; Bartels, D; Harberd, N; Flavell, R (Springer-Verlag, 1983)
cDNA clones encoding wheat HMW glutenin subunits have been isolated from a cDNA bank made to poly A(+) RNA from developing wheat endosperm var. Chinese Spring. One such clone, pTag 1290, has enabled us to identify the HMW glutenin mRNA species. The DNA sequence of this clone has been partially determined and it contains several tandem DNA repeats. The sequence is discussed in relation to the generation of the HMW glutenin subunit gene family. Analysis of the organization of the HMW glutenin sequences in the wheat genome revealed that the genes encoding HMW glutenin subunits exist in low copy number and are located on the long arm of each of the homoeologous group 1 chromosomes.